PENGARUH JUMLAH TENAGA KERJA, INVESTASI HIJAU, KONSUMSI, TEKNOLOGI DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN/KOTA PROVINSI SUMATERA BARAT - Yumia Ramadhona; Ansofino Ansofino; Yosi Eka Putri (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This type of research is quantitative research. Research data was conducted from 2019-2023 with a total of 95 samples. The data used in this research is secondary data. The techniques used in this research are documentation and literature study techniques with panel data regression analysis using the eviews program. The research results show that 1) the influence of the number of workers (X1) influences economic growth positively and is not significant; 2) Green investment (X2) has a positive and significant effect on economic growth; 3) Consumption (X3) has a positive and significant effect on economic growth; 4) Technology (X4) has a negative and insignificant effect on economic growth; and 5) The human growth index (X5) has no positive and significant effect on economic growth. 6) The number of workers, green investment, consumption, technology and the overall human growth index influence economic growth. The limitation of this research is that it only uses data from one region, so the data cannot be used to describe conditions in other regions or within a wider national scope.